Early automated infrared pupillometry is superior to auditory brainstem response in predicting neurological outcome after cardiac arrest. (September 2020) - Obinata, Hirofumi; Yokobori, Shoji; Shibata, Yasushi; Takiguchi, Toru; Nakae, Ryuta; Igarashi, Yutaka; Shigeta, Kenta; Matsumoto, Hisashi; Aiyagari, Venkatesh; Olson, DaiWai M.; Yokota, Hiroyuki
Abstract: Aim: Assessment of brainstem function plays a key role in predicting the neurological outcome after cardiac arrest. However, the relationship of the two quantitative brainstem assessment methods—automated infrared pupillometry (AIP) and auditory brainstem response (ABR)—with neurological prognoses remains unclear. This study compares the prognostic value of AIP and ABR after cardiopulmonary arrest. Methods: This retrospective observational study included 124 comatose patients after cardiopulmonary arrest. ABR and AIP measurements were performed simultaneously within 72 h after return of spontaneous circulation. Neurological outcome was assessed at discharge by estimating the cerebral performance category (CPC) score; favourable neurological outcome (CPC score, 1–2) or poor neurological outcome (CPC score, 3–5). The correlation of each AIP parameter and ABR I-V wave latency was tested using Pearson's product moment correlation coefficient, and the prognostic value was compared using the area under the receiver operating characteristics curve (AUC). Results: Pupillary light reflex (PLR) was not detected in 69 patients, and ABR wave V was not detected in 47 patients. All these patients had poor neurological outcome. Among those whose PLR and ABR could be measured, each AIP parameter had a tendency to be correlated with ABR I-V wave latency. Pupil constriction velocity provided the greatest AUC (0.819), with 81% sensitivity and 77% specificity. ABR I-V wave latency provided extremely low AUC (0.560). Conclusions: Although AIP and ABR were correlated, the AIP measures were superior in predicting the neurological outcome after cardiac arrest as compared with the ABR measures.